2008
DOI: 10.3733/ucanr.8143
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Health Info Sheet: Calcium

Abstract: What function does calcium have in the body? Calcium is a mineral used for numerous functions, including building bones and teeth, muscle contraction, blood clotting, maintenance of cell membranes, and nerve transmission. 1 Because most of the calcium in the body is found in the skeleton, calcium' s critical function in maintaining bone health receives much attention. What are the effects of calcium deficiency? Adequate intake of calcium is essential for maximizing bone density. Therefore, an inadequate intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Participants who consumed moderate levels of alcohol had a lower risk of hip fracture. Although, high consumption of alcohol increases in loss of calcium in urine which reduces the bone mass [50,51]. Moreover, a number of studies revealed that osteoporosis was not associated with daily exercise [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Participants who consumed moderate levels of alcohol had a lower risk of hip fracture. Although, high consumption of alcohol increases in loss of calcium in urine which reduces the bone mass [50,51]. Moreover, a number of studies revealed that osteoporosis was not associated with daily exercise [52,53].…”
Section: Discussionmentioning
confidence: 99%